Building more common wealth in a climate changed world. Issue 5 (3rd September 2021) - Wilkinson, Jane
ABSTRACT: Glaring inequality is a feature of the Commonwealth's diversity. Most countries of the Commonwealth are developing countries in regions with high exposure to climate change impacts. Its 25 Small Island Developing States and 14 least developed countries face disproportionately high exposure to adverse consequences and face water scarcity brought on by droughts and melting glaciers, floods, destructive tropical storms, storm surges and rising sea levels. The global COVID-19 pandemic has highlighted countries having systemic and interconnected exposure to exogenous threats like climate change. Examining the relationships between income, poverty and carbon inequality within the Commonwealth may offer insights on how stronger cooperation based on the principle of 'equality in partnership' could be implemented to mobilise more resources and action to tackle climate change.